2017
DOI: 10.7554/elife.21130
|View full text |Cite
|
Sign up to set email alerts
|

YAP is essential for mechanical force production and epithelial cell proliferation during lung branching morphogenesis

Abstract: Branching morphogenesis is a fundamental program for tissue patterning. We show that active YAP, a key mediator of Hippo signaling, is distributed throughout the murine lung epithelium and loss of epithelial YAP severely disrupts branching. Failure to branch is restricted to regions where YAP activity is removed. This suggests that YAP controls local epithelial cell properties. In support of this model, mechanical force production is compromised and cell proliferation is reduced in Yap mutant lungs. We propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 60 publications
9
114
0
Order By: Relevance
“…However, Yap target genes are not restricted to these categories, being also found to be quite diverse and context‐dependent, as demonstrated by the Yap regulation of Ajuba , Ankrd1 , Areg , and SGK1 (Dupont et al, ; Lange et al, ; Yoo, Kim, Chung, Hwang, & Lim, ; J. Zhang et al, ). For example, while Sox9 is upregulated by Yap in hepatocytes, there is no evidence that in the developing lung epithelium Yap gain or loss of function has any obvious impact in Sox9 expression (Lin et al, ; Mahoney et al, ; van Soldt et al, ; Yimlamai et al, ). Thus, a central question revolves around the ability of Yap to induce gene expression in a context‐dependent manner.…”
Section: Transcriptional Roles Of Yap/tazmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Yap target genes are not restricted to these categories, being also found to be quite diverse and context‐dependent, as demonstrated by the Yap regulation of Ajuba , Ankrd1 , Areg , and SGK1 (Dupont et al, ; Lange et al, ; Yoo, Kim, Chung, Hwang, & Lim, ; J. Zhang et al, ). For example, while Sox9 is upregulated by Yap in hepatocytes, there is no evidence that in the developing lung epithelium Yap gain or loss of function has any obvious impact in Sox9 expression (Lin et al, ; Mahoney et al, ; van Soldt et al, ; Yimlamai et al, ). Thus, a central question revolves around the ability of Yap to induce gene expression in a context‐dependent manner.…”
Section: Transcriptional Roles Of Yap/tazmentioning
confidence: 99%
“…Disruption of Yap in the lung epithelium of Shh Cre ; Yap f/f mice show that, although not required for specification of the distal progenitors, Yap is crucial to form the Sox2+ epithelial compartment. Indeed, analysis of Yap‐deficient lungs in vivo reveals a markedly truncated Sox2+ domain (airways) associated with large cyst‐like dilated Sox9+ distal buds (Lin et al, ; Mahoney et al, ; van Soldt et al, ). Interestingly, there is evidence suggesting that the Yap effects in Sox2 specification and airway morphogenesis are not fully interdependent.…”
Section: Transcriptional Roles Of Yap/tazmentioning
confidence: 99%
See 1 more Smart Citation
“…In cell collectives YAP/TAZ translocate to the nuclei of leader cells to regulate endothelial cell migration (Lin et al, 2017;Yu and Guan, 2013;Zhang et al, 2015;Mason et al, 2019;Neto et al, 2018)(and Suppl. Fig.…”
Section: Endothelial Dlc1 Controls Cell Orientation and Directed Migrmentioning
confidence: 99%
“…These data suggest that YAP/TAZ mediate feedback control of cytoskeletal and focal adhesion dynamics through the Rho-ROCK-myosin II pathway. We performed a meta-analysis of previously published ChIP-seq and gene expression data and identified SNF-like kinase 2 (NUAK2), Rho GTPase activating protein 28 (ARHGAP28), and ARHGAP29 as YAP/TAZdependent target genes [34][35][36][37] . We confirmed that YAP/TAZ regulate these putative targets by PCR of ECFC mRNA 1 hour after initiation of the wound assay.…”
Section: Yap/taz Regulate Nuak2 To Control Cytoskeletal Polymerizationmentioning
confidence: 99%